2016
DOI: 10.21101/cejph.a4534
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosols in the Suburbs of Ostrava during a One Year Period

Abstract: SUMMARYAim: The aim of this paper is to provide information about the concentrations of airborne bioaerosols (airborne bacteria, fungi and endotoxins) in outdoor suburban environments in Ostrava, Moravian-Silesian region, Czech Republic.Methods: The methods were based on systematic bioaerosol monitoring during one calendar year, subsequent analysis of the samples and statistical processing. The regression, correlation analysis and analysis of variance for one factor and pairwise comparisons were performed on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…We also recognize that the indoor DP levels are significantly associated with the outdoor DP levels ( r s = 0.627; P < .001) and that outdoor DP can affect the presence of indoor bioaerosols. A positive relationship between outdoor DP and outdoor bioaerosols was reported by Jiřík et al, and the association was more pronounced for fungi compared to bacteria 89 . A study by Ryan et al reported that an increase in bioaerosol concentration indoors is likely associated with higher indoor moisture due to outdoor moisture intrusion.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…We also recognize that the indoor DP levels are significantly associated with the outdoor DP levels ( r s = 0.627; P < .001) and that outdoor DP can affect the presence of indoor bioaerosols. A positive relationship between outdoor DP and outdoor bioaerosols was reported by Jiřík et al, and the association was more pronounced for fungi compared to bacteria 89 . A study by Ryan et al reported that an increase in bioaerosol concentration indoors is likely associated with higher indoor moisture due to outdoor moisture intrusion.…”
Section: Resultsmentioning
confidence: 77%
“…While higher bioaerosol concentrations are often associated with high levels of RH and temperature, 20,35‐37,40,47,86‐88 reliance on just RH or just on temperature is insufficient because taken separately, they do not reflect the amount of moisture in the air, which is an important factor for microbial growth 19 . Hence, we used DP (°C/°F) as an independent variable as it reflects water content in the air 89‐91 . The DP data were stratified by seasons and then by the buildings for each season (Figure 4 and Table 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have been conducted on the outdoor bioaerosols and given the exposure levels of ambient bacteria and fungi. [16][17][18] However, limited information is available on bacteria and fungi indoor exposure in China, especially in residences, offices, and schools, where people usually spend most of the time every day. 19 The geographic location and climate condition profoundly affect the concentration levels of bacteria and fungi, 20 but existing studies are usually limited to one city or one region, so a nationwide systematic review is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have been conducted on the outdoor bioaerosols and given the exposure levels of ambient bacteria and fungi 16‐18 . However, limited information is available on bacteria and fungi indoor exposure in China, especially in residences, offices, and schools, where people usually spend most of the time every day 19 .…”
Section: Introductionmentioning
confidence: 99%